Kedudukan ahli waris yang beralih agama terhadap harta warisan menurut hukum adat di Kecamatan Luwuk Kabupaten Banggai Sulawesi Tengah - AENI, A. Nur ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The purposes of this thesis with the title “The Status of Heirs Who Change Religious Toward The Heritage Based on The Traditional Law in Luwuk Subdistrict, Banggai Regency, Center Sulawesi” were to know the status of heirs who change religious toward the heritage and the factors that influence the religious change of heirs. This research had the characteristic of descriptive analysis that is describe the data and analyzes the social process which persisted and the meaning of the factas that was visible in the field beside using bibliography data. To collect data, it was used directly interview to the respondent and informants. The results of the research shows that: 1. The status of heirs who change religious toward the heritage based on the traditional law in Luwuk Subdistrict, Banggai Regency, Center Sulawesi was same in their proportion that was 1:1 with others although one of heirs had changed his / her religion. The process of heritage division could be implemented well before and after the heir passed away, and the media that has important role is family partnership, with the purpose to achieve agreement in dividing the heritage in order that there is no dispute in the future. 2. The were two factors that influenced the religious changing of an heir. First was environment where someone lives, grow up, make a change and always intense to interect on his or her social environment. A human is an “agen of change” for his or herself and it is not different from someone’s decision to change his or her religion because of environment factor where someone lives. Second was marriage. This factor most influences an heir changes religion because he or she follows his or her spouse’s religion.